2015
DOI: 10.1002/em.21965
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Pig‐a and micronucleus assays respond to N‐ethyl‐N‐nitrosourea, benzo[a]pyrene, and ethyl carbamate, but not pyrene or methyl carbamate

Abstract: This laboratory previously described a method for scoring the incidence of peripheral blood Pig-a mutant phenotype rat erythrocytes using immunomagnetic separation in conjunction with flow cytometric analysis (In Vivo MutaFlow®). The current work extends the method to mouse blood, using the frequency of CD24-negative reticulocytes (RET(CD24-)) and erythrocytes (RBC(CD24-)) as phenotypic reporters of Pig-a gene mutation. Following assay optimization, reconstruction experiments demonstrated the ability of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The increase in micronuclei in mice in the present study was highly consistent with results of a previous multiple dose micronucleus assay conducted in our laboratory (21). For the present study of rats and mice exposed to acrylamide we assessed the induction of chromosomal damage by using the in vivo micronucleus assay and mutation of an endogenous gene using a novel flow cytometry based assay that can detect mutation at the Pig-a locus in the blood of mice, rats and humans (38,(48)(49)(50). The Pig-a gene mutation assay is based on the loss of Pig-a, a gene whose product is essential for the synthesis of glycosylphosphatidylinositol (GPI) anchors on the cell surface of reticulocytes and red blood cells (51).…”
Section: Discussionsupporting
confidence: 73%
“…The increase in micronuclei in mice in the present study was highly consistent with results of a previous multiple dose micronucleus assay conducted in our laboratory (21). For the present study of rats and mice exposed to acrylamide we assessed the induction of chromosomal damage by using the in vivo micronucleus assay and mutation of an endogenous gene using a novel flow cytometry based assay that can detect mutation at the Pig-a locus in the blood of mice, rats and humans (38,(48)(49)(50). The Pig-a gene mutation assay is based on the loss of Pig-a, a gene whose product is essential for the synthesis of glycosylphosphatidylinositol (GPI) anchors on the cell surface of reticulocytes and red blood cells (51).…”
Section: Discussionsupporting
confidence: 73%
“…These results show that PCH elicits a robust mutagenic response in the bone marrow even at doses that do not produce cytotoxicity. While Phonethepswath et al () also reported PCH‐induced Pig‐a mutation in mice, it is not productive comparing those results with data reported herein because the previous study utilized an early mouse blood labeling protocol that is now understood to systematically underestimate mutant cell frequency (Labash et al ). Finally, Chen et al () recently reported strong induction of Pig‐a mutations following a 28‐day exposure regimen in rats using daily doses higher than those used here.…”
Section: Discussionmentioning
confidence: 65%
“…To the best of our knowledge, the in vivo mutagenic evaluation of Pyr has been conducted in the following 2 studies: rat Pig-a assay by Torous et al [16], and mouse Pig-a assay by Labash et al [24]. In both Pig-a studies, Pyr was reported to show no mutagenic effects.…”
Section: Discussionmentioning
confidence: 97%